Glycine max oil physical-chemical quality obtained of irradiated seeds - Valter Arthur (Brazilian Journal of Radiation Sciences, 2021)
Ionizing radiation applied to agriculture has mainly benefited food production, as it reduces natural losses caused by physiological processes, as well as eliminating or reducing microorganisms, parasites and pests. In addition, this technique also allows the production of mutants with characteristics of greater productivity, precocity, smaller size, greater resistance to diseases and pests. These mutants are used to obtain new varieties of species of agronomic interest. The objective of this study was to evaluate the physic-chemical quality of the oil extracted from seeds of G. max (soybean) obtained from irradiated seeds with different doses of gamma radiation (0, 25, 50, 75 and 100 Gy of a Cobalt-60 source, type Gammacell-220 installed in CENA-USP). The physic-chemical analyzes included: AOCS Cd-3d-63, AOCS Cd-3-25 and AOCS Cd-1-25, Acids Index (I.A), Saponification Index (IS), Iodide Index (II), respectively. All analytical determinations were performed at least in triplicates. The values found for I.A., for I.S. and for I.I., did not differ from the oil sample obtained from soybean seeds from control subjects (without irradiation) regardless of the concentration and dose of radiation applied to the seeds. The oil analyzed did not show physical-chemical variation in comparison with the oil obtained from non-irradiated seeds, thus suggesting the absence of modifications in these parameters after the genetic improvement induced by the radiation.